Penatalaksanaan Asuhan Keperawatan dengan Masalah Gangguan Oksigenasi pada Pasien Chronic Kidney Desease: OXYGENATION DISORDER PROBLEMS IN CHRONIC KIDNEY DISEASE PATIENTS - Syafrinanda, Virginia; Tiala, Nur Hijrah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: to analyze the management of nursing care with oxygenation disorders in Chronic Kidney Disease (CKD) patients.Methods: This research design uses a case study research design in the nursing care process starting from assessment, nursing diagnosis, nursing intervention, implementation and nursing evaluation. The target of the study was Mr. D with a diagnosis of Chronic Kidney Disease (CKD) with oxygenation disorders undergoing hemodialysis treatment.Results: The results of the assessment showed that Mr. D experienced severe shortness of breath marked by a respiratory rate of 26 x/minute, there was nose cupping. The main nursing diagnosis was ineffective breathing patterns related to respiratory effort obstruction marked by dyspnea. Nursing interventions included observation and therapeutic actions. Implementation and evaluation were carried out for 1x24 hours, it was found that Mr. D's shortness of breath decreased slightly, RR decreased from 26 x/minute to 24 x/minute.Conclusion: Implementastion nursing care management for patients experiencing oxygenation disorders will reduce the main problems felt by the patient.